PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING BERBASIS CANVA DALAM MENINGKATKAN KREATIVITAS BELAJAR SISWA DI SMK PASUNDAN 1 KOTA SERANG - Tomi Bustomi; Dewi Surani; Amat Hidayat (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
The development of computer and internet technology has triggered changes in the way we live starting from social interactions, commerce and banking. The Covid-19 pandemic in 2020 also increased the acceleration of human civilization into the era of industrial revolution 4.0 and 5.0 in a short time and has changed the way students learn. To welcome the era of society 5.0, Indonesia must have human resource competencies, one of which is creativity. This research aims to determine the application of the Canva-based Project Based Learning learning model in increasing student learning creativity at Pasundan I Vocational School, Serang City. This research uses classroom action research methods. This research design uses the Kemmis & Taggart model which consists of planning, acting and observing, reflecting components which are carried out repeatedly (cycles) for up to 3 cycles. This research found results namely the Application of Learning Models Project Based Learning Canva-based can increase student learning creativity, increased student creativity is supported by the long completion time for Canva application-based design projects of between 4-5 days; the existence of a WhatsApp group as a space for communication and sharing information, both tricks and tips about Canva and Design; as well as comfortable conditions and situations in every discussion and study both offline and online. EnhancementStudent Learning Creativity This occurred by 36% from 12% to 48% in cycle II and 36% from 58% to 84% in cycle III until students could meet the Minimum Completeness Criteria (KKM) of 75.